Strategic Nonviolent Power: The Science of Satyagraha - Mark A. Mattaini (Global Peace Studies, 2013)
Strategic Nonviolent Power is a unique and important contribution to a field that is flourishing in the current global milieu. Mattaini demonstrates a sweeping knowledge of the field of resistance studies as well as systems theory. I don't know of another study that does what this one does apply a new theoretical framework to nonviolent resistance, synthesize existing material, and provide numerous illuminating examples from history in a single book.